Surgical Complications of Arteriovenous Fistula as Permanent Vascular Access in Patients with End Stage Renal Disease at Gezira Hospital for Renal Disease and Surgery. Revisited - Mustafa, Altegane M A; M Elhag, Mohamed Elfatith; Taha, Sami M; M, M Nasr eldin; M Ahmed, M El Imam (Gezira Journal of Health Sciences, 2017)
Background: Vascular access (VA) is a mainstay to perform an efficient hemodialysis (HD) procedure. Objectives: To evaluate the surgical complications of AV fistula as permanent vascular access in a patient of end stage renal disease (ESRDS) at Gezira hospital for renal diseases and surgery ( GHRDS ) . Methods: Retrospective, prospective cross sectional hospital based study, done in 237 patients with end stage renal disease who underwent arteriovenous fistula.In 206 patients of the study sample done retrospectively and 31 patients of the study sample done prospectively,and they were followed for 1year. Study was conducted from September 2010 to September 2016. Data was collected using questionnaire.   Results: Sixty eight percent of study sample were males, with 42% above 50 years and 0.8% less than 10 years. Most of the patients (52.3%) were diagnosed as ESRD from the first presentation, 43.5% were diagnosed as chronic renal failure (CRF) on regular followup, while the minor rest of the patients were due to acute renal failure(ARF) which progressed to end stage renal disease.The complications rate was 32.8% (n=82), perioperative complications were 9.3% (n=22) represented as infections 3.8% (n=9), bleeding 3.0% (n=7), stenosis 1.7% (n=4), thrombosis 0.8% (n=2). The late complications were 23.18% (n= 60) the commonest was pseudo aneurysmal 19.4% (n=46) followed by venous HTN 0.8% (n=2) and steal syndrome 0.4%(n=1), skin necrosis 0.4%(n=1), idiopathic stop function 2.1% (n=5), thrombosis 0.4% (n=1). Conclusion: Permanent arteriovenous fistula is the best option for haemodialysis in patients with end stage renal disease. The commonest complication was puncture site pseudo aneurysm.